Optical assay for glucose based on the luminescnence decay time of the long wavelength dye Cy5™ - Tolosa, Leah (Sens Actuators B Chem, 1998)
An optical assay for glucose is described based on the luminescence decay time of a long wavelength dye (Cy5) which can be excited with currently available red laser diodes. Concanavalin A was covalently labeled with Cy5 which served as the donor in an assay based on fluorescence resonance energy transfer (FRET). The acceptor was Malachite Green which was covalently linked to insulin which served as a carrier protein. To provide binding affinity for ConA Malachite Green insulin was also covalently labeled with maltose (MIMG). Binding of Cy5ConA to MIMG resulted in a decreased intensity and decay time of Cy5 as observed by time-correlated single photon counting. Glucose was detected by competitive displacement of MIMG from Cy5ConA, resulting in increased intensity and decay time. This glucose assay has several features which can result in practical real world assays for glucose. The long absorption wavelength of Cy5 allows excitation with red laser diodes, which can be readily pulsed or amplitude-modulated for time-domain or frequency-domain decay time measurements. Additionally, decay times can be measured through skin using long wavelength excitation and emission, suggesting the possibility of an implanted glucose sensor. And finally, the assay affinity and reversibility can in principle be adjusted by controlling the extent and type of sugar labeling of the carrier protein.